Public cowboy no. 1 the life and times of Gene Autry - George-Warren, Holly (Oxford ; New York : Oxford University Press, 2007)
The only performer to earn five stars on the Hollywood Walk of Fame--for film, recordings, television, radio, and live performance--Gene Autry was the singing cowboy king. Journalist George-Warren offers the first serious biography, tracing Autry's climb from farm boy to multimillionaire. Autry's loving mother died on the brink of her son's success, while his ne'er-do-well father married five times and wandered the West. Autry battled his own demons but emerges here as one of America's most charitable benefactors, known for his boundless generosity, and a patriot who enlisted during World War II. The book provides colorful details of Autry's lengthy radio and recording career; his movie career, where he breathed new life into the Western genre; and his role in early television, the first movie star to develop his own TV shows. Along the way, he invested shrewdly, becoming the only entertainer listed among 1990's Fortune 400.--From publisher description.
The Autrys and the Ozments -- Cross timbers -- Tioga -- Workin' on the railroad -- Musical mentors -- A new name, a new profession -- The Oklahoma yodeling cowboy -- Hillbilly recording artist -- Midwestern buckaroo -- Uncle Art -- From "High steppin' Mama" to "Silver haired daddy" -- Sweet home Chicago -- "The singing and yodeling marvel" -- Motherless son -- WLS radio star -- Cowboy balladeer -- Smiley, Patsy, and Pee Wee -- Celluloid cowboy -- Negotiations by post -- Republic pictures star -- Battles--on screen and off -- The singing cowboy -- Public cowboy No. 1 -- Strike! -- At home and abroad -- Melody ranch -- A town called Gene Autry -- War! -- Sergeant Gene Autry -- Don't fence me in -- Back in the saddle -- Gene Autry, Inc. -- From horses to reindeer, from big screen to small -- Last of the pony riders -- On the road again--and again -- The last round-up.
Includes filmography: p. [382]-385.
Includes discography: p. [337]-381.
Includes bibliographical references (p. [303]-336) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2023. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Autry, Gene, -- 1907-1998.; Motion picture actors and actresses -- United States -- Biography; Singers -- United States -- Biography; Electronic books